Suatu Repetisi Mengenai Implementasi Kejujuran, Kesetiaan Dan Integritas Terhadap Pembentukan Karakter: Studi Kata “'ĕ-mū-nāh” Dalam Amsal 12:17, 22 - Pattinaja, Aska Aprilano; Sualang, Farel Yosua (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
In the book of Proverbs, the word "'ĕ-mū-nāh" appears only twice, namely Proverbs 12:17 and Proverbs 12:22. Interestingly, the word "'ĕ-mū-nāh" in this text is interpreted by scholars with different meanings, with Waltke translating it as "honesty," Fox seeing it as "commitment," Longman, interprets it as "loyalty," Ross sees it as "social justice," and Clifford translates it as "righteousness." The question becomes, what is the true meaning of this word? In its development, the meaning of this word is often translated generally based on the context of the verse, without paying attention to the specific elements of wisdom literature structure. Therefore, this study aims to examine the meaning of the word "'ĕ-mū-nāh" which actually refers to repetition or levels of character change. Based on the hermeneutic study method of the sub-genre of wisdom literature, this study found several meanings of the word "'ĕ-mū-nāh", namely: first, honesty; second, loyalty; and third, integrity. The implementation of this research is for every believer to repetition good character changes, starting from honesty to loyalty, from loyalty to integrity based on moral ethics according to the truth of God's Word.